Class-II division-I malocclusion treated with extraction of maxillary first premolars- a case report - Jahan, Hasnat; Hossain, Md Zakir; Rahman, Muklesur (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
This case report describes the treatment of a 13 years old girl named FahrialSharmin came to Dhaka Dental College with complaints of moderate maxillary proclination. She had class-II molar and canine relationship and showed 12 mm overjet and 5.5 mm overbite with lip trap.Treatment started with extraction of maxillary first premolars and fixed orthodontic therapy. Treatment were finished in a class-II molar relationship with canine guidance and ideal overjet& overbite relationships were established. The final result was esthetically well balanced. Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.23-24